Sosialisasi Penerapan Bahan Ajar Kimia Berbasis Etnokimia Sasambo Pada Guru-Guru SMA Di Kabupaten Lombok Timur - Andayani, Yayuk; Idrus, Syarifa Wahidah Al; Rahmawati; Hidayanti, Ermia; Listantia, Nora; Febrianti, Nia (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Improving students’ understanding of chemistry can be supported by learning resources linked to everyday life, such as integrating chemistry with local wisdom. Yet, many teachers still face challenges in identifying scientific concepts within Sasambo ethnochemistry due to limited knowledge of its types, processes, and meanings. To address this issue, a socialization program was conducted to strengthen teachers’ understanding of the application of Sasambo-based ethnochemistry teaching materials. The program involved 31 chemistry teachers from both public and private high schools in East Lombok Regency, representing diverse age ranges and teaching experiences. The activity received positive responses from participants. Results of the pretest and posttest revealed a significant shift from the low knowledge category to the good and very good categories. This indicates that the socialization effectively enhanced teachers’ comprehension of both the concepts and applications of ethnochemistry in chemistry instruction. These findings highlight that socialization serves not only as a medium for knowledge transfer but also as an initial step in preparing teachers to design contextual teaching resources systematically, rooted in local cultural values.